Analisis Kesantunan Berbahasa dalam Kegiatan Diskusi pada Pembelajaran Bahasa Indonesia Mahasiswa Ilmu Komunikasi Angkatan 2021 A Universitas Abdurrab - Anita, Fenny; Murny (GERAM: Gerakan Aktif Menulis, 2022)
Language politeness is a rule of behavior that is determined and mutually agreed upon by a particular community. In learning in the classroom requires a polite attitude to communicate, especially in discussion activities. This study was conducted to explain the language politeness of Communication Studies students 2021 A in discussion activities on Indonesian language learning at Abdurrab University. . This type of research is a qualitative research with descriptive method. This research was conducted on students of Communication Studies at Abdurrab University. The data of this research is in the form of utterances spoken by the research subjects. The subject of this research is a student of Communication Science batch 2021 A Abdurrab University. The data collection techniques in this study were tapping techniques, listening-engagement techniques, recording techniques and note-taking techniques. Based on the results of the study, it can be concluded as follows: Indonesian language politeness in the presentation and discussion activities of Communication Science students class 2021 A Abdurrab University that there is compliance with Geoffrey Leech's politeness principles, because from (185) speech data, there are (173) speech data of Indonesian language politeness compliance, or in other words, it has a high politeness compliance rate, which is 93.5%, and there are (12) speech data on politeness violations in Indonesian or in other words it has a low politeness violation rate of 6.5%.